Diagnóstico de desempeño laboral de los titulados en la carrera de informática de la ESPAM MFL en el sector público. - Mejía Muñoz, Ángela Isabel (2017)
The purpose of the research was to diagnose the level of job performance of public servants graduated in the ESPAM MFL from the computer science career, as a contribution to continuous improvement within the activities carried out; the graduates under study were also identified, performance evaluation instruments applied by the Ministry of Labor to the public servants were also examined, the level of performance of the graduates under study was determined, a statistical analysis of the results were obtained. The research methods were: the deductive method that allowed through logical reasoning to know the research problem and the different aspects of the profile of the graduate, the historical method served to compile data of methodological information in books, scientific articles among others, the analysis applied in the documentation, Delphi to validate the experts who participated in the research and give reliability to it, Kendall for the selection of quality indicators that should have these professionals; techniques such as descriptive statistics allowed to obtain accurate cause-and-effect results to identify possible causes that affect the level of work performance in the public sector; in which an analysis of the results of form MRL-01 was carried out, which is based on indicators of management of the position, a statistical tool was applied that determined the level of performance of professionals.